Evapotranspiration-Based Irrigation for Agriculture: Sources of Evapotranspiration Data for Irrigation Scheduling in Florida - Isaya Kisekka; Kati Migliaccio; Michael D. Dukes; Bruce Schaffer; Jonathan H. Crane; Kelly Morgan (EDIS, 2010)
AE455, a 4-page fact sheet by Isaya Kisekka, Kati W. Migliaccio, Michael D. Dukes, Bruce Schaffer, Jonathan H. Crane, and Kelly Morgan, lists some of the public sources of ETo data for irrigation scheduling in Florida. Includes references. Published by the UF Department of Agricultural and Biological Engineering, January 2010.